Cryopreservation of epididymal semen of domestic cat - S. Ya. Amstislavsky; E. Yu. Brusentsev; V. I. Mokrousova; E. A. Kizilova; V. V. Kozhevnikova; V. A. Naprimerov; I. N. Rozhkova (Вавиловский журнал генетики и селекции)
Domestic cat (Felis silvestris catus) is used as a model species for developing effective methods of wild felids’ semen cryopreservation. The present study represents a comparison of domestic cat semen cryopreservation with two commercially available cryoprotectant agents (CPAs): CaniPlus Freeze (CPF) and SpermFreeze (SF). Semen was collected from the caudal epididymises of adult males and frozen with CPF and SF, correspondingly. The viability of frozen-thawed spermatozoa was evaluated by VitalScreen kit, staining with hematoxylin and eosin was performed for analysis of the spermatozoa morphology; both analyses were combined with the light microscopy. The viability rate of the frozenthawed semen cryopreserved with CPF and SF did not differ: 32.3±4.4 % for CPF and 43.3±4.0 % for SF. Total percentage of morphologically normal spermatozoa after freezing and thawing domestic cat semen was 26.0±2.3 % for CPF and 23.9±1.9 % for SF. In both cases, there were no differences from non-frozen semen, in the latter group the total percentage of spermatozoa with normal morphology was 29.0±4.1 %. The most frequent anomalies were the anomalies of tail, and the rarest anomalies were head defects. The percentages of spermatozoa with anomalies of the head, mid piece, tail and combined did not differ in these three groups. Taken together these results suggest that both CPAs are suitable for the purpose of domestic cat semen freezing and cryopreservation, although CPF was designed for Canidae semen cryopreservation and SF was developed for human semen freezing and so far was used exclusively in reproductive medicine. It might be concluded that these two commercially available cryoprotectant media are applicable for the purposes of domestic cat breeds’ semen cryopreservation.